Non-Surgical Root Canal Treatment of Dens Invaginatus 3 in a Maxillary Lateral Incisor - Moradi, Saeed; Donyavi, Zakyeh; Esmaealzade, Mohammad (Iranian Endodontic Journal, 2008)
The aim of this case report was to describe the clinical management of an unusual dens invaginatus type 3. A case of dens invaginatus in a maxillary lateral incisor with a periapical lesion is reported. The patient presented with pain and localized swelling. Despite the complex anatomy and diagnosis of dens invaginatus, non-surgical root canal treatment was performed successfully. Key Learning Points:- Dens invaginatus may be presented in different forms, and the etiology of this phenomenon is not fully understood. - Due to abnormal anatomical configuration, dens invaginatus presents technical difficulties in its clinical management. - Non-surgical root canal treatment can be performed successfully.